Culturally grounded pathways to sustainable agricultural investment in Papua - Sumule, Agus; Ludia Wambrauw; Purnomo, Dwi Wasgito; Fretes, Yance de (Edelweiss Applied Science and Technology, 2025)
This study explores the cultural foundations necessary for sustainable agricultural investment in Papua, Indonesia, with a focus on indigenous Melanesian communities. The purpose is to examine how legal recognition of land rights intersects with cultural legitimacy to shape investment acceptance. A qualitative methodology was employed, combining legal document analysis with semi-structured interviews involving tribal leaders, policymakers, NGO workers, and community representatives. Findings reveal a persistent gap between formal legal frameworks and practical implementation, where laws acknowledging indigenous land rights are inconsistently enforced. Investment legitimacy depends not only on legal compliance but also on alignment with core cultural values such as kinship, reciprocity, and ancestral stewardship. Community-supported mechanisms like voluntary contributions and endowment funds emerge as culturally accepted investment tools. The study concludes that sustainable investment must be embedded in community-led, culturally rooted approaches supported by participatory governance. Practical implications include the need for policy reforms that integrate Free, Prior, and Informed Consent (FPIC), strengthen adat-based institutions, and establish transparent, inclusive financial mechanisms. These findings offer a culturally grounded framework for ethical, inclusive agricultural investment in indigenous territories.